Improving The Quality of Competency of Hindu Religion Teachers Through Teacher Working Group in Denpasar City - Ni Komang Sutriyanti; I Made Luwih (Jurnal Penjaminan Mutu, 2019)
Teachers have a very significant role in improving the quality of education, notably at the level of basic education that equips students with the ability to provide basic knowledge and skills. Teacher working group of Hinduism which is as a spot for teachers of Hinduism at the elementary school level in professional teacher training and helping to solve problems faced in carrying out the learning process needs to get the attention of various parties. Therefore, this paper attempted to examine the teacher's competency in relation to the teacher working group with the title of “Improving the Quality of Competency of Hindu Religion Teachers through Teacher Working Group in Denpasar City”. This paper used the qualitative research method, the location of the research was in the Hindu teacher working group spot in Denpasar City, the type of data was descriptive, with primary and secondary data sources, the informant determination techniques used purposive sampling technique, data collection methods used observation, interviews, literature studies, and documentation, as well as used data analysis techniques. The results of the study showed that, first, the form of activity of the Hindu Teachers Working Group in Denpasar, namely holding workshops, conducting routine meetings, and carrying out Tirtayatra. Second, the constraints and efforts made in improving the competence of Hinduism teachers are human resources and infrastructure. By Karen, the struggles made were to hold workshops as an effort to promote the human resources of teachers as professionals, and efforts to rent places and infrastructure so that activities could run well. Third, the role of the teacher working group in improving the competence of Hindu religion teachers is to play a role in four Hindu religious teacher competencies, namely pedagogical competence, personality competence, social competence, and professional competence.